Effects of work values on resistance to organizational change - İnançoğlu, Evren (My University, 1999)
Günmüzde, örgütsel değişim örgütler için kaçınılmaz ve hayati bir kavram haline gelmiştir. Bunun sebebi örgüt elemanlarındaki ve örgütün sürekli etkileşim içerisinde bulunduğu çevresindeki sürekli ve hızlı değişimdir. Değişim ihtiyacına giren örgütler için 'değişim yönetimi' önemli bir hal alır. Yani, örgütler değişime neden olan sebebleri, ona duyulan ihtiyaçları belirlemeye ve bu ihtiyaçları giderebilecek yeni fikirler aramaya başlarlar. Değişim yönetimi, bu ihtiyaçları giderecek değişim çalışmalarının uygulama safhasındaki her aktiviteyi bünyesinde barındırmaktadır. Örgütler, değişimden önce değişim isteyen güçler ile değişime direnç güçleri arasında bir denge halindedir. Bu nedenle değişim çalışmalarının başarılı olması için bu dengenin değişim isteyen güçler lehine bozulması gerekmektedir. Değişim çalışmalarının uygulama safhasında değişimi uygulayanların karşısına, değişim yönetiminin negatif olgularından biri olan 'değişime direnç' çıkmaktadır. Bu nedenle araştırmacılar, değişime direnci anlamak ve onu kırıp yeni bir denge oluşturmak için birçok araştırmalar yapmışlardır. Çalışma hayatı insan hayatındaki en önemli olgulardan biridir. Dolayısı ile insanlar her alanda olduğu gibi çalışma hayatında da bir takım değerlere sahip olurlar. Bu değerler, çalışanlara, örgütün amaçlarına ulaşma çabalarında neyin doğru ve uygun neyin ise yanlış ve uygun olmayacağı konusunda rehberlik eder. Örgütsel değişimde, başarılı bir değişim için çalılanların birtakım değerlerini değiştirmeleri gerektiği bilinen bir gerçektir. Ancak, çalışanların sahip oldukları değerlerin değişime direnç ile bir ilişkisi olup olmadığı bilinmemektedir. Bu araştırma için önemli olan bu iki kavram, --çalışma değerleri ve değişime direnç- bir açıdan bir araya getirilmek ve anlamlı bir ilişki kurulmak istenmiştir. Bu noktadan hareketle, bu araştırmanın amacı, kişilerin çalışma değerlerinin, örgütsel değişime olan direnci artıracağını veya azaltacağını ıspatlamaktır.

Today, organizational change became a vital and inevitable concept for the organizations which continually change as their environments and their members change. This organizational change which comes out with the continuos interactions of the organizations with their environments, made it essential to understand the reasons for change, to find out the need for change and to create solutions to satisfy the need for change.These change studies to satisfy the need for change are all part of change management. It gained a lot of importance in recent years because rapid changes in the external environment have demanded rapid changes within the organizatıon. Organizations may be in a state of equilibrium, with forces pushing for change on the one hand and forces resisting change by attempting to maintain the status quo on the other. Kurt Levin expressed this phenomenon in his field force theory which suggests that an equilibrium is maintained by driving forces and restraining forces. In initiating change, the tendency is to increase the driving forces. Those may indeed produce some movement, but it usually also increases resistance by strengthening the restraining forces. Since resistance to change is very important in organizational change a lot of researches have been carried out to understand , reduce or eliminate the restraining forces and then move to a new level of equilibrium. Since work is the one of the most important aspect of the life, people also develop some values at work like other values they develop at the rest of their time. Value can be defined as a fairly permanent belief about what is appropriate and what is not that guides the actions and behavior of employees in fulfilling the organization's aims in other words values can be thought of as forming an ideology that permeates everyday decisions. It is known that organizational change can not occur without an explicit effort to reeducate people to adopt new values at work however it is not certain whether these work values have any effect on the resistance to organizational change. In this study, it is aimed to prove that the work values have an effect on the resistance to change. According to this correlation the resistance to a change in an orgnization will depend on the values of the people at that organization. To test this hypothesis, a change resistance scale will be given to the people in an organization to determine whether they will accept or resist a probable change idea and a work values scale will be given to the same individuals to determine their values. I.
Keywords: Örgütsel Değişim